Assessing the level of digital literacy among selected Malaysian school teachers / Mohammad Fazli Baharuddin, Mohamad Noorman Masrek and Shamila Mohamed Shuhidan - Baharuddin, Mohammad Fazli; Masrek, Mohamad Noorman; Mohamed Shuhidan, Shamila (Faculty of Information Management, 2023)
As a whole, focusing on digital literacy can enable teachers to educate students on how to utilize the opportunities offered by digital technology to enhance students critical thinking and creativity, and engage in their lives in ways that can make their learning more meaningful. Despite the fact that digital literacy continues to grow in importance as a crucial ability in education, a lack of digital literacy on the part of teaching staff is regarded as a genuine concern in preparing students for successful careers. Hence, the objective of the study to investigate how teachers perceive their digital literacy skills. The survey research approach was utilised to collect data through a self-administered questionnaire. The data was statistically analysed using descriptive analysis based on 356 valid responses. The findings revealed that Malaysian teachers believe that they have a high degree of digital literacy. Therefore, proper policymaking and planning for teachers on how to evaluate the quality of information in digital media, as well as improving their skills in identifying relevant information among the vast amount of available information by using the right search strategy, can help teachers achieve optimal digital literacy.